An investigation of the effect of relative humidity on viscoelastic properties of flax fiber reinforced polymer by fractional-order viscoelastic model. (January 2023) - Xu, Bowen; Blok, Rijk; Teuffel, Patrick
Abstract: As an environmental-friendly material with eligible mechanical properties, FFRP (Flax Fiber Reinforced Polymer) composites are being widely studied and used in the construction industry. This paper presents an investigation of the effect of environmental humidity on the viscoelastic properties of FFRP. Frequency sweep tests are conducted, and results are re-organized by the Time-Temperature Superposition Principle (TTSP). The Huet-Sayegh viscoelastic model is introduced to describe the relationship between viscoelastic properties and loading frequency. The fractional derivative is applied to the model for more accurate results. It is found both storage modulus and loss modulus decrease with the increase of relative humidity. However, the loss factor does not have a monotonical correlation with the relative humidity of the environment. In general, it can be concluded both the capacity of FFRP to store and dissipate the energy decreases over the hygroscopicity absorption in the air, but there is no specific relationship between the amount of their reduction. Graphical abstract: Image 1 Highlights: Flax fiber reinforced polymer (FFRP) composites were prepared and tested in environments with different relative humidity. Frequency sweep test in tensile mode wre conducted on FFRP. Huet-Sayegh model with fractional differential order were applied to study tensile viscoelastic behavior of FFRP. Relationship between viscoelastic properties of FFRP and relative humidity in a wide loading frequencies were investigated.